Marketing Analysis of Product-Harm Crises on Brand Switching (Case Study on Honda eSAF Frame) - Mulyadi, Mulyadi; Ariska, Emalia; Azhari, Azhari; Muchsin, Muchsin (Ekonomis: Journal of Economics and Business, 2025)
This research aims to analyze the impact of marketing factors, such as brand equity and product quality, on Brand Switching behavior through Product-Harm Crises, with a case study of the Honda eSAF motorcycle frame fracture incident. This crisis not only affects technical aspects but also damages the reputation and consumer trust in Astra Honda Motor (AHM). The study uses the SEM-PLS method with a sample of 160 respondents. Results show that brand equity and product quality have a significant influence on product crises, but do not directly or indirectly trigger consumers to switch brands through these product crises. The decision for Brand Switching turns out to be more complex and influenced by factors other than product crises. Therefore, companies need to develop effective crisis mitigation strategies to maintain consumer loyalty and reduce the risk of brand switching, in addition to strengthening brand equity and product quality.